The selection of teaching/learning materials in health sciences education : report of a WHO Study Group [on the Selection of Teaching/Learning Materials in Health Sciences Education ; Geneva, 10-16 April 1973. - World Health Organization (Geneva : World Health Organization, 1974)
Welke lesmaterialen kies je best wanneer je gezondheidsonderwijs wil geven?